ความสัมพันธ์ระหว่างความหลากหลายและการกระจายตัวของแมลงน้ำ ร่วมกับคุณภาพน้ำในลำธารต้นน้ำแม่แจ่ม อำเภอกัลยาณิวัฒนา จังหวัดเชียงใหม่ - ทากัน รุ่งนภา; คุณประดิษฐ์ ทัตพร (Science Essence Journal, 2017)
บทคัดย่อ การศึกษาครั้งนี้ได้มีวัตถุประสงค์เพื่อศึกษาความสัมพันธ์ความหลากหลายและการกระจายตัวของแมลงน้ำ ควบคู่กับคุณภาพน้ำในลำธารต้นน้ำแม่แจ่ม อำเภอกัลยาณิวัฒนา จังหวัดเชียงใหม่ ได้ทำการกำหนดจุดเก็บตัวอย่าง 4 จุด ได้แก่ MJ1 MJ2 MJ3 และMJ4 เก็บตัวอย่าง 3 ครั้งในเดือนธันวาคม พ.ศ. 2557 พฤษภาคม พ.ศ. 2558 และสิงหาคม พ.ศ. 2558 โดยใช้วิธีเก็บแมลงน้ำด้วย D-frame net รวมถึงวัดค่าคุณภาพน้ำทางเคมี และกายภาพบางประการ จากผลการศึกษาพบแมลงน้ำทั้งหมด 8,889 จาก 9 อันดับ 84 วงศ์ โดยพบแมลงน้ำในอันดับ Diptera (54%) มากที่สุด รองลงมาคือ Ephemeroptera(26%) Coleoptera (8%) Trichoptera (6%) Odonata (4%) Hemiptera (3%) และอื่นๆ (<1%) ตามลำดับ ดัชนีความหลากหลายสูงสุด 2.564 ที่ MJ1 ต่ำสุดที่ MJ2 มีค่า 0.921 ค่าดัชนีความสม่ำเสมอในการกระจายตัวสูงสุดที่ MJ1 มีค่า 0.638 ต่ำสุดที่ MJ2 มีค่า 0.521 จากการประเมินความชุกชมสัมพันธ์พบว่าวงศ์ Chironomindae เป็นสิ่งมีชีวิตชนิดเด่น และการประเมินคุณภาพน้ำทางชีวภาพด้วย BMWPThai score และ ASPT และการประเมินคุณภาพน้ำจืดผิวดิน พบว่าคุณภาพน้ำในแต่ละจุดเก็บตัวอย่างอยู่ในเกณฑ์คุณภาพน้ำปานกลางถึงค่อนข้างดี - - - The Relationship between Diversity and Distribution of Aquatic Insect with Water Quality of Mae Chaem Headwater streams, Kanlayaniwattana District, Chiang Mai Province ABSTRACT The aim of this study is to assess the relationship between diversity and distribution of aquatic insect with water quality in Mae Chaem headwater stream, Kanlayanitwatta district, Chiang Mai. Aquatic macroinvertebrates were sampled at Mae Chaem wadeable-headstream at four sites including MJ1, MJ2, MJ3 and MJ4 from December 2014 to August 2015 using D-frame net and obtained some physico-chemical parameter of water quality. A total of 8,889 individuals belonging to 84 families and nine orders were examined. The most aquatic insect abundance were Diptera (54%), Ephemeroptera (26%), Coleoptera (8%), Trichoptera (6%), Odonata (4%), Hempitera (3%) and others (<1%) respectively. The highest diversity index was recorded at MJ1, 2.564 and lowest diversity index was recorded at MJ2, 0.921. The highest evenness index was found at MJ1, 0.638 and lowest evenness index was found 0.521. In terms of the relative abundance, the most abundant taxa recorded was Chironomidae. The use of biological indices as BMWPThai score and ASPT and physical and chemical parameters of standard fresh-water surface to evaluate water quality showed that the water quality was moderate to good quality in each sampling sites.